The Effect of Learning Science, Technology, Engineering, and Mathematics (STEM) on the Ability to Understand the Material Concepts of Lines and Angles - Anggini Dinda Nursafitri; Nurul Anriani (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
This research is motivated by the low ability to understand mathematical concepts of junior high school students. One effort to improve students' ability to understand mathematical concepts is to use a Science, Technology, Engineering and Mathematics (STEM) learning approach that encourages students to be able to open their mindsets in finding new knowledge, developing creativity, and making students active explorers by doing the mathematical activities directly with the facilities prepared by the teacher during the learning process. This research was conducted at SMP Negeri 21 Serang in 2021/2022 which aims to determine the effect of learning Science, Technology, Engineering and Mathematics (STEM) on the ability to understand mathematical concepts of junior high school students on line and angle material. The research method used in this study is a quasi-experimental design with the nonequivalent pretest-posttest control group type of design. This study involved two classes consisting of experimental and control classes. The sample of this study was class VII D, which consisted of 30 students as the experimental class and VII A, which consisted of 30 students as the control class. The experimental class applies the STEM learning approach and the control class applies conventional learning. The instrument used is in the form of a test description of the ability to understand mathematical concepts. The data from this study were analyzed using descriptive statistics and inferential statistics. Based on the results of the research that has been done, it can be concluded that the final achievement and improvement of students' ability to understand mathematical concepts using the STEM learning approach in learning mathematics is better than students using conventional learning. Thus, the Science, Technology, Engineering and Mathematics (STEM) learning approach can be applied to improve the ability to understand mathematical concepts of junior high school students.